Satisfaction of Employees in the Organisation from Frederick Laloux Model Perspective - Bujas, Jan (Satysfakcja pracowników a typ organizacji w perspektywie modelu Fredericka Laloux, 2024)
Nowadays employee satisfaction is becoming more and more important for companies. Managers and boards of directors started to realise that the effectiveness of the business is strictly connected with the individual performance of each unit involved in processes of the organisation. The aim of the paper was to examine the correlation between employee satisfaction and the type of organisation from the Frederick Laloux model perspective. His theory assumes that organisations have an evolutionary character and evolve with the people who make them up. He listed several types of organisations and marked each with a color. According to Laloux’s concept, the more evolutionary the type of organisation, the greater the emphasis on employee satisfaction. The study was conducted in a quantitative form. A questionnaire was used as a research tool to collect data. The research proved that the hypothesis mentioned above is true and people that belong to more evolved types of organizations are indeed more satisfied.
Bujas, J. (2024). Satisfaction of Employees in the Organisation from Frederick Laloux Model Perspective. W J. Radomska & A. Witek-Crabb (Red.), New Trends in Business Management (s. 24–33). https://doi.org/10.15611/2024.30.7.02
Keywords: employee satisfaction; types of organisations; Laloux's model; colors of organisations; motivation; satysfakcja pracownika; typy organizacji; model Laloux; kolory organizacji; motywacja